2009
DOI: 10.1177/1078155209102336
|View full text |Cite
|
Sign up to set email alerts
|

Severe hiccups during chemotherapy: corticosteroids the likely culprit

Abstract: Hiccups generally are self-limiting and of short duration. Those lasting more than 48 h or recurring at frequent intervals are termed persistent. There are numerous causes of hiccups, with medications implicated only rarely. While hiccups are usually benign, severe attacks may lead to exhaustion, eating difficulties, and affect quality of life. We report a case of severe hiccups in a patient receiving chemotherapy (oxaliplatin, 5-fluorouracil, leucovorin) for metastatic colorectal cancer. Hiccups began on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In our study, 3 (10.69%) of the patients reported hiccups, 2 (1.8%) of which lasted for 3 days; the other resolved in 24 hours. While hiccups are usually benign, severe attacks may lead to exhaustion, eating difficulties, and affect quality of life (57). Several authors reported dysphonia following steroid injections (58-60) but none of them as well used dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 3 (10.69%) of the patients reported hiccups, 2 (1.8%) of which lasted for 3 days; the other resolved in 24 hours. While hiccups are usually benign, severe attacks may lead to exhaustion, eating difficulties, and affect quality of life (57). Several authors reported dysphonia following steroid injections (58-60) but none of them as well used dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for treatments involving steroids [35], drugs that are commonly used in medicine, including dental medicine. Being able to recognize the potential “drug-hiccup link” will better prepare health care practitioners manage any unexpected complications.…”
Section: Discussionmentioning
confidence: 99%
“…Most AEs were mild or moderate in intensity. The most frequently observed TRAEs were hiccups [35,88], constipation and headache [36,44], AEs that are associated with the class effects of 5-HT 3 RAs (headache and constipation) [31], NK 1 RAs and high-dose steroids (hiccups) [94,95].…”
Section: Efficacy Of Nepamentioning
confidence: 99%